Physicochemical Properties and Catalytic Performance of Sulphonic Resins of Various Morphological Types in Ethyl t-Butyl Ether Synthesis - Nina V. Vlasenko; Yuri N. Kochkin; Tamila G. Serebrii; Peter E. Strizhak (Adsorption Science & Technology)
Physicochemical and catalytic properties of sulphonic resins of various morphological types in ethyl t -butyl ether synthesis were studied. We have found that the turnover frequency (TOF) of sulphonated cation-exchange resins reflects the effect of morphology expressed in terms of fractal geometry. The correlation between the catalytic activity of various types of sulphonated resins and their fractal dimension was established. Difference in observed TOF of sulphonic resins of various morphological types is caused by various accessibilities of acid sites. Catalysts of more ordered structure (characterized by smaller fractal dimension) provide the best conditions for the adsorption–desorption of reactants and products resulting in large values of TOF.